Neonatal congenital heart surgery: contemporary outcomes and risk profile - Ahmed Abdelrahman Elassal; Osman Osama AL-Radi; Ragab Shehata Debis; Zaher Faisal Zaher; Gaser Abdelmohsen Abdelmohsen; Mazen Shamsaldeen Faden; Nada Ahmed Noaman; Ahmed Ragab Elakaby; Mohamed Esam Abdelmotaleb; Ahmed Mostafa Abdulgawad; Mohamed Saleh Elhudairy; Abdulla Husain Jabbad; et al. (Journal of Cardiothoracic Surgery, 2022)
Abstract Objective Many studies still dispute the identification of independent risk factors that influence outcome after neonatal cardiac surgery. We present our study to announce the contemporary outcomes and risk profile of neonatal cardiac surgery at our institute. Methods We designed a retrospective study of neonatal patients who underwent surgery for congenital heart diseases between June 2011 and April 2020. Demographic, operative, and postoperative data were collected from medical records and surgical databases. The primary outcome was the operative mortality (in-hospital death) and secondary outcomes included hospital length of stay, intensive care unit stay, duration of mechanical ventilation. Results In total, 1155 cardiac surgeries in children were identified; of these, 136 (11.8%) were performed in neonates. Arterial switch operations (48 cases) were the most frequent procedures. Postoperatively, 11 (8.1%) patients required extracorporeal membrane oxygenation, and 4 (2.9%) patients had complete heart block. Postoperative in-hospital mortality was 11%. The median postoperative duration of mechanical ventilation, intensive care unit stay, and hospital length of stay were 6, 18, and 24 days, respectively. Conclusion The early outcomes of neonatal cardiac surgery are encouraging. The requirement of postoperative extracorporeal membrane oxygenation support, postoperative intracranial hemorrhage, and acute kidney were identified as independent risk factors of mortality following surgery for congenital heart defects in neonates.